Business Plan for Real Estate Consultancy Company in Baku, Azerbaijan - Humbatli, Leyla (ADA University, 2022)
The presented paper explores the business plan for real estate consultancy company with architectural planning and technical evaluation advantages. The company offers its clients a unique and individual approach according to its requirements by selecting the real estate, evaluating the technical aspects of the building, and providing space planning options. Within the provided services the company also conducts real estate market research, communicates to external parties and arranges property viewings. Even though the real estate and architecture industries are closely related to each other, the real estate investors/home buyers are constrained to work separately with two parties during different stages. This creates a reality of unsatisfied customers due to lack of technical competences at a time of decision making. Along with the clients, real estate agents also have insufficient knowledge in architecture to understand the needs and requirements of their clients and point to the right directions. The goal of this research is to shape the business opportunity, asses the financial feasibility and generate a well-built business plan for BAY consulting. The research results reveal the need of consulting services to lessen the stress from real estate search process and to avoid further frustration for clients. The financial projections validate the feasibility of the business idea and demonstrates that the company can ensure sustainable growth and generate profit
Keywords: Real estate business -- Planning; Business planning -- Azerbaijan; Real estate investment -- Consulting services; Business